Meta-Synthesis: The Influence of Mathematical Anxiety on Critical Mathematical Thinking - Cahya, Nabella Dwi; Mariani, Scolastika; Agoestanto, Arief; Masrukan (JRPM (Jurnal Review Pembelajaran Matematika), 2024)
The purpose of this research is to describe the influence of mathematics anxiety on students' mathematical critical thinking abilities. The research method used in this study was meta-synthesis, a qualitative systematic review that analyzed four relevant articles with the research title. The steps involved formulating the research problem, followed by searching for previous relevant research with the same title and then analyzing it in depth. The data collection technique used non-tests by examining previous research with similar problems to obtain results and conclusions. The study surveyed 4 articles, consisting of 3 national journal articles and one international journal article. The analysis of the four related articles resulted in the conclusion that math anxiety has a negative impact on students' mathematical critical thinking abilities.